KEBIASAAN PENCUCIAN RASKIN DAN RESIDU ZAT PEMUTIH (KLORIN) DI KELURAHAN SIDORAME TIMUR KECAMATAN MEDAN PERJUANGAN KOTA MEDAN TAHUN 2013 - adelina irmayani lubis; zulhaida Lubis; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
The estimated, there are chlorine used in the Raskin which received by people in the village of East Sidorame because has a white color, not much grain is broken, and it has little sting smell. The aim of this study is to describe the habit of  washing Raskin and the residual chlorine in Raskin in the village of East Sidorame. This is the descriptive survey study, with Raskin and the poor family who receive it as a sample. Measurement of chlorine is using argentometry method. The sample is taken with systematic random sampling for 84 families who getting and consuming the Raskin. Base on the laboratory test show that the chlorine found in the Raskin. It has 17,70% chlorine before washing. After the first wash of rice, there was chlorine content decreased to 14,16%, the second wash decreased to 10,18%, the third wash to 5,75%, and the fourth wash, chlorine content decreased to 3,98%. Almost the people wash the rice by stirring the rice and draining water at same time while washing the rice. 38,55% of them washing the rice once. 31,33% of them washing the rice twice. Almost of them washing rice once or twice, but there is still chlorine in great enough quantities if compared washing Raskin to four times. Suggested for Bulog to attention to the quality of rice which distributed to people in terms of food security in rice. Recommended to people to washing Raskin to fourth wash or more to reduce residual chlorine. Keyword : Raskin, Chlorin, Washing Raskin